مسؤولية المنظمة في ظل حوكمة الشركات دراسة ميدانية على سوق دمشق للأوراق المالية - دشلي, كمال (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعد الاستراتيجية منهجاً وإطار عمل تستطيع المنظمة من خلاله تحقيق أهدافها، حيث تواجه العديد من المنظمات المعاصرة العديد من التحديات الاجتماعية والاقتصادية والبيئية، إضافةً إلى المنافسة والتطور التكنولوجي مما أفرز الحاجة إلى تطبيق حوكمة الشركات وهذا بدوره يتطلب من المنظمة تطوير استراتجياتها لتلبية متطلبات أصحاب المصالح فيها بالتطبيق السليم لمبادئ حوكمة الشركات. وتوصل الباحث إلى عدد من النتائج أهمها: أن هناك تأثيراً متبادلاً بين شفافية الإفصاح المحاسبي وحوكمة الشركات، وأن هناك بعض الالتزامات الاجتماعية والبيئية يجب على الإدارة الوفاء بها. This strategy can be considered as a course and framework through which the Organization can achieve its goals. Current organizations face lots of social economical and environmental challenges in addition to the competition and the technological progress, something which caused urgent needs for applying Corporate Governance which also requires from the organizations Side, developing its Strategies to meet the requirements of the Stakeholders for a correct application of the principles of corporate Governance. The researcher comes up with many important results, the most important of which is that (i) there is an exchanged influence between transparency of accounting disco lour and the corporate governance, and that (ii) there are many social and environmentat obligations which the management must meet.